Consumers' attitudes toward TV advertising in Malaysia : a descriptive study - Yee, Han How (1999)
Advertising is an important social phenomenon. It both stimulates consumption and economic activities and models life-styles and a certain value orientation. Consumers are confronted with numerous advertisements in multiple media. Everyone seems to hold an opinion about various aspects of advertising, ranging from informative and amusement to cynicism and condemnation. This study intends to examine consumers' attitudes toward TV advertising; whether they like or dislike TV advertising. A model adopted from Pollay and Mittal has been modified to assess consumers' attitudes toward TV advertising in Malaysia by looking into personal and societal factors. The findings revealed that in general, Malaysian still hold positive attitudes toward TV advertising. In addition, this study suggested that personal and societal factors are better instrument to differentiate those who like or dislike TV advertising rather that demographic characteristics alone. As a conclusion, even though Malaysian still has favorable attitudes toward TV advertising, precaution should be taken to prevent audience erosion in future.